Kajian Pengeringan Bak Gabah Secara Intermittent Terhadap Mutu Beras - Maulidin, Achmad Fitrah; Nelwan, Leopold Oscar; Hasbullah, Rokhani (Jurnal Keteknikan Pertanian, 2020)
Grain drying with bed dryer is generally effective with high temperatures, but this can increase fissured rice percentage. This can be overcome by combining drying method with tempering. These study were aim to examine drying temperature and duration on bed dryer using intermittent high temperature dryer, and its effect on quality variety of Ciherang with 20-22% moisture content. These research method consists of drying treatment without tempering using 35°C, 60°C and 80°C temperatures to 14% moisture content. Drying treatment with tempering consists of initial drying process-initial tempering-second drying- second tempering or without tempering, where the first drying temperature were 80°C for 20 minutes, 60°C for 30 minutes and second drying temperature were 60 °C and 35°C to 14% moisture content. The tempering duration used was 90 minutes. Results showed the grain drying method without tempering 35°C gave the highest percentage of head rice. However, the use of tempering had significantly reduced cracking and increased head rice percentage compared without tempering at the same temperature. Initial drying of 60°C for 30 minutes-tempering for 90 minutes-drying both temperatures of 35°C to 14% moisture content had been able to produce high head rice and low fissured rice percentage respectively 81.41% and 10%.